2022
DOI: 10.3390/foods11030455
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Future of Edible Insects in Europe

Abstract: The effects of population increase and food production on the environment have prompted various international organizations to focus on the future potential for more environmentally friendly and alternative protein products. One of those alternatives might be edible insects. Entomophagy, the practice of eating insects by humans, is common in some places but has traditionally been shunned in others, such as European countries. The last decade has seen a growing interest from the public and private sectors to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 43 publications
(95 reference statements)
1
50
0
Order By: Relevance
“…Nowadays, due to the researchers increased interest to have quality protein with less impact on the environmental conditions, significant steps have been made forward the valorization of edible insects. Insects, compared to conventional animals are offering superior or similar nutritional qualities with fewer requirements on water, feed, and land [ 1 ]. Their chemical composition rich in proteins, essential amino acids, fatty acids, minerals, and vitamins make them an optimum source of nutrition, being consumed by 2.5 billion people worldwide [ 2 ] in more than 110 countries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, due to the researchers increased interest to have quality protein with less impact on the environmental conditions, significant steps have been made forward the valorization of edible insects. Insects, compared to conventional animals are offering superior or similar nutritional qualities with fewer requirements on water, feed, and land [ 1 ]. Their chemical composition rich in proteins, essential amino acids, fatty acids, minerals, and vitamins make them an optimum source of nutrition, being consumed by 2.5 billion people worldwide [ 2 ] in more than 110 countries [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, edible insects could be considered a sustainable source in many regions such as South and Central America, Australia Papua New Guinea, and South-East Asia region [ 5 ], being able to deal with global food security problems [ 3 ]. It is expected that the consumption of edible insects will increase by 47% between 2019 and 2026, mainly in Europe and North America [ 1 ]. In fact, in 2018, the European Food Safety Authority (EFSA) recognized insects as novel foods through the Regulation (EU) 2015/2283, and the Food Agriculture Organization (FAO) recommended including them in Western diets, aiming to cover the nutritional population gaps in proteins and fats [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While emerging research has demonstrated the health benefits of edible insects, including antimicrobial, nutritional, and therapeutic properties [ 29 ], few studies have evaluated implementation of an edible insects programs among populations vulnerable to malnutrition. Most research advocating for edible insect consumption are observational studies on traditional practices [ 30 ], including in Madagascar [ 31 ], the Democratic Republic of Congo [ 32 ], and Thailand [ 33 ], or acceptability studies in Western countries without traditions of edible insects [ 34 ]. Acceptability studies in Liberia and Ghana have shown important stakeholders, including caregivers, patients, community leaders, and healthcare professionals, to have favorable opinions towards palm weevil larvae farming as a source of nutrition [ 19 , 24 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to review performed by Dagevos [ 100 ], Westerners remain hesitant to include insect eating in their daily diet, and consequently, the evidence suggests that the eating of insects is anything but widespread and common, but rather surrounded by unfamiliarity and reluctance. That is why Mancini et al [ 107 ] suggested that most of the demand for edible insects will be from the feed sector.…”
Section: Crucial Aspects Of Edible Insect Marketingmentioning
confidence: 99%